The Influence of Content Quality and Influencer Credibility on Consumer Trust in Shopping on Shopee - Mohamad Rizki Eda Javier; Annisa Sanny; Hidayati Purnama Lubis (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the influence of content quality and influencer credibility on consumer trust in shopping on the Shopee e-commerce platform. This research employs a quantitative approach using a survey method. Primary data were collected through an online questionnaire distributed to 100 active Shopee users. Data analysis was conducted using multiple linear regression with SPSS version 25. The results indicate that content quality has a positive and significant effect on consumer trust, influencer credibility has a positive and significant effect on consumer trust, and both content quality and influencer credibility simultaneously have a significant effect on consumer trust. These findings highlight the importance of influencers in building consumer trust through high-quality content and strong credibility in e-commerce platforms.